2017
DOI: 10.5306/wjco.v8.i5.378
|View full text |Cite
|
Sign up to set email alerts
|

Further the liquid biopsy: Gathering pieces of the puzzle of genometastasis theory

Abstract: Metastasis is the major cause of mortality in cancer disease and still constitutes one of the most controversial mechanism, not yet fully understood. What is almost beyond doubt is that circulatory system is crucial for cancer propagation. Regarding this system, much attention has been recently paid to liquid biopsy. This technique is aimed to detect circulating tumor cells (CTCs) and circulating nucleic acids so it can be used as a tool for diagnostic, prognostic and follow-up of patients. Whereas CTCs tend t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 82 publications
(94 reference statements)
0
21
0
2
Order By: Relevance
“…134,135 The observation that cfDNA could integrate into the genomes of healthy cells led to the development of the genometastasis hypothesis. [134][135][136][137][138] However, further studies showed that the uptake of vesicles that contain DNA depends on the condition of the cell recipient. For example, transformed cell line variants are more sensitive to exosome-mediated uptake than other cell lines.…”
Section: Transforming Ability and Functional Modulation Of Other Cellsmentioning
confidence: 99%
“…134,135 The observation that cfDNA could integrate into the genomes of healthy cells led to the development of the genometastasis hypothesis. [134][135][136][137][138] However, further studies showed that the uptake of vesicles that contain DNA depends on the condition of the cell recipient. For example, transformed cell line variants are more sensitive to exosome-mediated uptake than other cell lines.…”
Section: Transforming Ability and Functional Modulation Of Other Cellsmentioning
confidence: 99%
“…Blood-based tests, also known as liquid biopsy, can offer a potential alternative measure that overcomes the problems posed by traditional methods. Liquid biopsy such as circulating tumor cells or circulating cell-free DNA (cfDNA) constitutes a promising and less invasive technique [ 4 ]. However, no satisfactory blood-based markers for RCC currently exist, creating an urgent need for the identification of new molecular markers.…”
Section: Introductionmentioning
confidence: 99%
“…Другим возможным механизмом формирования плюрипотентного фенотипа у опухолевых клеток может быть феномен «генометастазирования» [176]. Предполагается, что экстраклеточная двуцепочечная ДНК, выделившаяся из клеток, погибших в результате апоптоза или некроза, как первичного, так и вторичного, может поглощаться раковыми клетками, прошедшими первые стадии дифференцировки/коммитирования, но еще сохранившими такую базовую характеристику СРК, как способность захватывать фрагменты экстраклеточной двуцепочечной ДНК.…”
Section: существует ли третий вариант: обсуждениеunclassified